PENGARUH PERMAINAN BALOK ANGKA TERHADAP KEMAMPUAN MENGENAL LAMBANG BILANGAN 1-10 PADA ANAK KELOMPOK A - Sari, Dwi Maya; Abdullah, M Husni (PAUD Teratai, 2016)
Abstract : The background of this research was from the low ability of the children of pronouncing, pointing, arranging in a series, and relating number from 1 to 10. From of observation, it showed that the children not do the teacher?s instruction well when the teacher?s asked them to set the numbers in a series. The purpose of this research was to find out an effect from the number cube game towards the ability to know numbers.The research used the quantitative approach with pre- experimental design, using one-group pre-test and post-test. The subjects of this research were 20. The data were collected by observation of the game instrument. The result were analyzed by using non-parametric statistics with wilcoxon match pair test in which the counted Tcount< Ttable. The result of it showed that the application of the game was significant since there was a noticed effect from the two variables it the counted Tcount< Ttable.The result shows that the average score was 7 before treatment and 13 after the treatment. It was found that Tcount = 0 was less than Ttable = 52 or it can be said that the alternative hypothesis (Ha) is accepted because Tcount< Ttable (0 < 52) and null hypothesis (Ho) is refused because Tcount> Ttable (0>52). Therefore, it can be concluded that there is an influence of the appied game was very significant for the ability of the children to identify number of group A children in Ikmal Ceria kindergarten Labuhan Sreseh, Madura. It proves that the game could help the children?s cognitive ability especially in indetifying numbers Keywords: Cube Game, Number, Kindergarten Abstrak : Penelitian kuantitatif ini bertujuan untuk membuktikan pengaruh permainan balok angka terhadap kemampuan mengenal lambang bilangan. Populasi penelitian berjumlah 20 anak. Metode pengumpulan data menggunakan observasi dengan alat permainan. Analisis data menggunakan statistik non parametik uji jenjang Wilcoxon (wilcoxon match pairs test) dengan rumus t hitung< t tabel, dimana penelitian ini dikatakan signifikan karena adanya pengaruh dua variabel jika thitung< t tabel. Berdasarkan hasil analisis data tentang kemampuan mengenal lambang bilangan pada saat observasi sebelum perlakuan (pretes) dan observasi setelah perlakuan (postest) menggunakan permainan balok angka diperoleh nilai rata-rata hasil pre tes 7 dan rata-rata hasil postes 13. Hasil perhitungan dengan uji jenjang diperoleh t hitung= 0 lebih kecil dari t tabel = 52 dan hasil pengambilan keputusannya yaitu : Ha diterima karena t hitung< t tabel(0<52) dan Ho ditolak karena t hitung> t tabel(0>52). Simpulan penelitian menunjukkan bahwa permainan balok angka berpengaruh secara signifikan terhadap kemampuan mengenal lambang bilangan pada anak kelompok A TK Ikmal Ceria Labuhan Sreseh?Sampang. Kata kunci : Balok-balok angka, Lambang bilangan, Taman kanak-kanak